Skeletal muscle vasodilatation during maximal exercise in health and disease - Calbet, Jose A L (Blackwell Science Inc, 2012)
Maximal exercise vasodilatation results from the balance between vasoconstricting and vasodilating signals combined with the vascular reactivity to these signals. During maximal exercise with a small muscle mass the skeletal muscle vascular bed is fully vasodilated. During maximal whole body exercise, however, vasodilatation is restrained by the sympathetic system. This is necessary to avoid hypotension since the maximal vascular conductance of the musculature exceeds the maximal pumping capacity of the heart. Endurance training and high-intensity intermittent knee extension training increase the capacity for maximal exercise vasodilatation by 20–30%, mainly due to an enhanced vasodilatory capacity, as maximal exercise perfusion pressure changes little with training. The increase in maximal exercise vascular conductance is to a large extent explained by skeletal muscle hypertrophy and vascular remodelling. The vasodilatory capacity during maximal exercise is reduced or blunted with ageing, as well as in chronic heart failure patients and chronically hypoxic humans; reduced vasodilatory responsiveness and increased sympathetic activity (and probably, altered sympatholysis) are potential mechanisms accounting for this effect. Pharmacological counteraction of the sympathetic restraint may result in lower perfusion pressure and reduced oxygen extraction by the exercising muscles. However, at the same time fast inhibition of the chemoreflex in maximally exercising humans may result in increased vasodilatation, further confirming a restraining role of the sympathetic nervous system on exercise-induced vasodilatation. This is likely to be critical for the maintenance of blood pressure in exercising patients with a limited heart pump capacity.